False-positive findings on 6-[18F]fluor-l-3, 4-dihydroxyphenylalanine PET (18F-FDOPA-PET) performed for imaging of neuroendocrine tumors. Issue 2 (August 2018) - Berends, Annika M A; Kerstens, Michiel N; Bolt, Janne W; Links, Thera P; Korpershoek, Esther; de Krijger, Ronald R; Walenkamp, Annemiek M E; Noordzij, Walter; van Etten, Boudewijn; Kats-Ugurlu, Gursah; Brouwers, Adrienne H; van der Horst-Schrivers, Anouk N A
Abstract : Background/aim: PET with 6-[18F]fluor-l -3, 4-dihydroxyphenylalanine ( 18 F-FDOPA) has been shown to be a useful imaging tool with a high sensitivity for the visualization of neuroendocrine tumors (NETs). 18 F-FDOPA uptake in tumors other than NETs has been suggested previously, but data on this phenomenon are limited. We therefore studied the non-physiological, false-positive uptake of 18 F-FDOPA in a large population of patients with a NET or with a high clinical suspicion of harboring a NET. Patients and methods: Retrospective single-center study among adult patients in whom 18 F-FDOPA PET scintigraphy was performed between January 2004 and December 2014. The original scan report was compared with the original pathology report corresponding with the 18 F-FDOPA PET-positive lesion. In case this was inconsistent with the diagnosis of a NET, both the scan and the pathology slides were reassessed. Specimens of these non-NET tissues were immunohistochemically stained for AADC. Results: 1070 18 F-FDOPA PET scans from 705 patients were evaluated. Focal or multiple 18 F-FDOPA-avid lesions were described in 709 18 F-FDOPA PET scans (66%). Histology of these 18 F-FDOPA PET-positive lesions was present in 508 (72%) cases. In seven cases, the histopathology was not compatible with NET but showed squamous cell carcinoma of the cervix, multiple myeloma (two cases), hepatocellular carcinoma, Schwannoma, adrenocortical carcinoma and a skeletal myxoid chondrosarcoma, with positive immunohistochemical staining for AADC in 67%. Conclusions: Pathological uptake of 18 F-FDOPA does not always indicate the presence of a NET. The possibility of 18 F-FDOPA uptake by tumor types other than NETs, although rare, should be considered.